2014
DOI: 10.3748/wjg.v20.i19.5666
|View full text |Cite
|
Sign up to set email alerts
|

Reduced genome size ofHelicobacter pylorioriginating from East Asia

Abstract: Helicobacter pylori (H. pylori), a major pathogen colonizing the human stomach, shows great genetic variation. Comparative analysis of strains from different H. pylori populations revealed that the genome size of strains from East Asia decreased to 1.60 Mbp, which is significantly smaller than that from Europe or Africa. In parallel with the genome reduction, the number of protein coding genes was decreased, and the guanine-cytosine content was lowered to 38.9%. Elimination of non-essential genes by mutations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…These results indicate that H. pylori strains have coevolved with their hosts, observations which are supported by results indicating that H. pylori has undergone reductive evolution during its association with man [ 11 ]. However, prolonged coevolution is commonly associated with commensal adaptation and concurrent loss of virulence [ 12 , 13 ]. Because H. pylori exhibits strain-specific virulence and potential to cause disease, this supports a model in which the coevolution of H. pylori and its cognate human host has been perturbed [ 2 , 3 ].…”
Section: H Pylori Infection and Disease Outcommentioning
confidence: 99%
“…These results indicate that H. pylori strains have coevolved with their hosts, observations which are supported by results indicating that H. pylori has undergone reductive evolution during its association with man [ 11 ]. However, prolonged coevolution is commonly associated with commensal adaptation and concurrent loss of virulence [ 12 , 13 ]. Because H. pylori exhibits strain-specific virulence and potential to cause disease, this supports a model in which the coevolution of H. pylori and its cognate human host has been perturbed [ 2 , 3 ].…”
Section: H Pylori Infection and Disease Outcommentioning
confidence: 99%
“…Besides undergoing phylogeographic differentiation, genomic analyses have revealed that H. pylori has, like other obligate human pathogens including Chlamydia trachomatis and Mycoplasma pneumoniae , undergone reductive evolution by reducing both the number of open reading frames (coding region sequences) and the total size of its genome [ 23 25 ]. This likely occurred as a consequence of its coevolution within the human host which provides a specialized niche for bacterial colonization and proliferation and consequently reduces the need to maintain genes involved in vital processes such as macronutrient synthesis and acquisition [ 26 ].…”
Section: Evolution Of H Pylori and Geographic mentioning
confidence: 99%
“…Studies comparing the characteristics of the H. pylori genomes isolated from different human populations show differences in size, gene number, and G+C content. Additionally, several segments are acquired by recombination and cause divergence of some genes in certain H. pylori phylogroups (Kawai et al, 2011;Yahara et al, 2013;Dong et al, 2014). These observations raise the question of whether there could be specific interactions between a determined phylogroup of H. pylori and human hosts in a given human population.…”
Section: Introductionmentioning
confidence: 99%